PENGARUH TERPAAN TAYANGAN SIBAK A1 PADANG TV TERHADAP PENGETAHUAN HUKUM MASYARAKAT KECAMATAN KOTO TANGAH - Sari, Anissa Kumala; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The mass media is very instrumental in the development or even changes in behavior pattrns of the public. According to S-R theory, the mass media has a direct, immediate and direct effect on the communicant. One of the mass communication media is television, compared to other mass media television has a special characteristic that is a combination of image and listening media that are informative, entertainment, and education. The purpose of the study was to determine how much influence the broadcast of Sibak A1 Padang TV on the legal knowledge of the people of Koto Tangah District.This research uses quantitative research methods, with data collection techniques, namely trough the distribution of questionnaires with the type of closed questionnaire. The data analysis technique used in this study is Simple Linear Regression Analysus. The number of respondents is 166 people determined trough simple random sampling technique, using the formula unknown population.The results of this study indicate that the magnitude of the influence of the Sibak A1 Padang TV show on the community's legal knowledge of Koto Tangah District is quite strong. This can be seen from the summary model table showing that the coefficient of determination (R2 ) obtained was 0.637 and the coefficient of determination (Rsqure) was 0.406. this figure shows the understanding that the influence of exposure to Sibak A1 Padang TV on the legal knowledge of the Koto Tangah District Community is 40.6 % with a moderate or quite strong category. While the remaining 59.4 % was influenced by other variables not included in this study.